2011
DOI: 10.2176/nmc.51.713
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Superficial Temporal Artery Pseudoaneurysm in Elderly Women -Three Case Reports-

Abstract: Three women older than 75 years presented with spontaneous superficial temporal artery (STA) pseudoaneurysms manifesting as a pulsatile mass in the preauricular region. None of the patients had a history of trauma. Histological examination of the surgically removed masses identified pseudoaneurysms based on the presence of connective tissue and adventitia. Spontaneous STA pseudoaneurysms are extremely rare. We suggest that all 3 aneurysms were associated with latent dissection and external force exerted by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…Although no universally accepted classification of STA aneurysms based on their etiology has been established, they have been classified as traumatic, iatrogenic, and spontaneous. [ 2 3 5 7 8 10 12 13 14 15 16 18 19 21 22 ] In our discussion, we use the designation traumatic and spontaneous (nontraumatic) aneurysms to describe traumatic- and iatrogenic aneurysms. Schechter and Gutstein[ 18 ] reported that 92% of STA aneurysms were traumatic, and the other 8% were spontaneous.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although no universally accepted classification of STA aneurysms based on their etiology has been established, they have been classified as traumatic, iatrogenic, and spontaneous. [ 2 3 5 7 8 10 12 13 14 15 16 18 19 21 22 ] In our discussion, we use the designation traumatic and spontaneous (nontraumatic) aneurysms to describe traumatic- and iatrogenic aneurysms. Schechter and Gutstein[ 18 ] reported that 92% of STA aneurysms were traumatic, and the other 8% were spontaneous.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] Spontaneous aneurysms, on the other hand, are true aneurysms that tend to be associated with arteriosclerosis. [ 14 21 ] Very rarely, spontaneous STA aneurysms are histologically dissecting aneurysms or pseudoaneurysms. Fujii et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this phenomenon has been described in 1 previous case series, these were 3 elderly female patients with more proximal lesions of the superficial temporal artery. 8,9 Nii et al 8 surmised a possible association with minor repetitive trauma of wearing eyeglasses. Patient 1 and the female patients studied by Nii et al 8 shared a similar lesion location at the proximal superficial temporal artery that is not classic for the most vulnerable portion of the superficial temporal artery prone to PA arising from blunt trauma.…”
Section: Discussionmentioning
confidence: 99%
“…1,7 Spontaneous formation of PAs of the superficial temporal artery has been reported, but it is thought to be extremely rare. 8 A PA presents clinically as a compressible, pulsatile mass, which can be painful, growing in size, and at times associated with headaches. The differential diagnosis includes lipoma, hematoma, cyst, abscess, lymph node, hemangioma/vascular malformation, or other soft tissue mass.…”
mentioning
confidence: 99%